A study on consumer movement and consumer protection in the western countries and Türkiye - Sağnak, F. Gül Aygen. (Thesis (Ph.D.) - Bogazici University. Institute of Social Sciences, 1997., 1997)
The purpose of this study is to find out about the developmental issues of consumer protection in our country from the perspectives of consumers, the business world, and related institutions (public institutions, quasi-public institutions, private sector institutions and consumer associations). Views and opinions of each group with respect to the general subject of consumer protection are believed to reveal future expectations related to the subject and also opportunities and limitations we are likely to be confronted with, as a nation, in reaching a better life. The study is composed of two main parts: The first part consists of the historical developments and current trends in the area of consumer protection in the United States, the European Union, and Tiirkiye together with the literature review for the years 1960-1995. The second part is on the field survey inclusive of statistical analyses of questionnaires filled out by 385 consumers, 45 respondents in private sector companies, and 30 respondents in related institutions together with qualitative comparison of responses of the three groups. The computer program SPSS / PC (Statistical Package for the Social Sciences) has been used in analyzing the data. Frequency distributions, Chi-square, t-test, F-test, Mann-Whitney test, and KruskalWallis test have been employed for analysis of results. Qualitative comparison of the consumer, manufacturer, and related institutions samples revealed that in general the three parties shared opinions regarding the topic of consumer protection and consumer related issues in Tiirkiye. Among the three groups, consumers and respondents in related institutions appeared to share ideas to a greater extent than manufacturers. However, agreement rates of respondents in all groups were considerably high in case of importance given to consumer rights, importance attributed to subjects in the topic of consumer protection, evaluation of ways to improve the prevailing situation of consumers, choice of the most constructive programs in responding to consumerist pressures, expectations regarding the future of consumers with respect to certain issues, and ranking of the various groups a company was thought to be socially responsible to. Statistical analyses conducted in the case of the individual samples did not yield much difference within the samples, either with respect to attitudes related to the general topic of consumer protection or consumer related issues in our country. In the case of the consumer sample, most of the differences in opinions seemed to exist between respondents living in the different districts of the city, respondents with different education levels, and respondents with different income levels. In the case of the manufacturer sample, most of the differences in opinions seemed to exist between respondents who thought the impact of the consumer protection movement to be very much on their company versus those who thought this impact not to be very much. In the case of the related institutions sample, regardless of the institution they worked for, respondents shared the same opinions to a very large extent with respect to the subject of consumer protection, in general. The study ends with implications for consumers, the business world, the State and related institutions, and for further research.
Keywords: Consumer protection -- Turkey.; Consumers.